2007
DOI: 10.1037/0033-2909.133.4.557
|View full text |Cite
|
Sign up to set email alerts
|

Stigma, obesity, and the health of the nation's children.

Abstract: Preventing childhood obesity has become a top priority in efforts to improve our nation's public health. Although much research is needed to address this health crisis, it is important to approach childhood obesity with an understanding of the social stigma that obese youths face, which is pervasive and can have serious consequences for emotional and physical health. This report reviews existing research on weight stigma in children and adolescents, with attention to the nature and extent of weight bias toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
934
3
45

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,105 publications
(1,026 citation statements)
references
References 183 publications
(368 reference statements)
29
934
3
45
Order By: Relevance
“…It is important to stress at this point that it is not being suggested that childhood obesity is without negative consequence. Childhood obesity is clearly associated with a range of adverse physical, psychological and social outcomes (7,(59)(60)(61)65) . In addition, the tracking of adiposity and related behaviours from childhood to adulthood increases the risk of morbidity and mortality related to chronic disease in adulthood.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to stress at this point that it is not being suggested that childhood obesity is without negative consequence. Childhood obesity is clearly associated with a range of adverse physical, psychological and social outcomes (7,(59)(60)(61)65) . In addition, the tracking of adiposity and related behaviours from childhood to adulthood increases the risk of morbidity and mortality related to chronic disease in adulthood.…”
Section: Resultsmentioning
confidence: 99%
“…However, there have been few attempts to compare methodologies, particularly in their potential to favour negativity (Jarvie et al, 1983). A second feature of the present research was the concurrent collection of children's attribute ratings and their choices between body shapes, with the aim to compare these methods in their assessment of negativity.There is conflicting evidence of gender differences (respondent and target character) in young children's negative stereotyping (Cramer & Steinwert, 1998;Dunkeld Turnbull et al, 2000), and uncertainty whether this is related to the trait or attitude assessed, e.g., the nature of being mean or victimizing differing between boys and girls (Puhl & Latner, 2007). This contrasts with much clearer evidence of gender differences in older children and adolescents (Rees, Oliver, Woodman, & Thomas, 2011).…”
mentioning
confidence: 99%
“…Reviewing the literature on weight stigma in children and adolescents, Puhl and Latner (2007) distinguish educators, parents, and peers as the primary sources of weight bias. The rejection of an obese target (usually a drawing or cartoon) as a friend, someone to play with, or to date, is common to many studies of teens and younger.…”
mentioning
confidence: 99%
“…Given evidence that weight-based stigma can itself worsen health (Muennig and Bench, 2008;Puhl and Latner, 2007), these findings should give us pause. Our findings suggest that researchers, journalists, activists, and politicians would benefit from understanding the potential negative consequences of messages representing these frames.…”
Section: Resultsmentioning
confidence: 99%